2022
DOI: 10.1101/2022.09.13.507732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sorting of droplets at kHz rates using absorbance activated acoustic sorting

Abstract: Droplet microfluidics allows one to address the ever-increasing demand to screen large libraries of biological samples. Absorbance spectroscopy complements the golden standard of fluorescence detection by label free target identification and providing more quantifiable data. However, this is limited by speed and sensitivity. In this paper we increase the speed of sorting by including acoustofluidics, achieving sorting rates of target droplets of 1 kHz. We improved the devices design for detection of absorbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Also, since the sorting uses Arduino-like microcontrollers, improvement in hardware will result in increased computation speed whilst retaining the accessibility of being inexpensive and opensource. Complementary work by Richter et al 29 has shown increased sorting throughput and removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity. We envision that a further upgrade to AADS designs could incorporate design improvements from both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the sorting uses Arduino-like microcontrollers, improvement in hardware will result in increased computation speed whilst retaining the accessibility of being inexpensive and opensource. Complementary work by Richter et al 29 has shown increased sorting throughput and removal of droplet trace artifacts by using a combination of surface acoustic waves and microlenses in the form of an optical air cavity. We envision that a further upgrade to AADS designs could incorporate design improvements from both studies.…”
Section: Discussionmentioning
confidence: 99%